Use of rapeseed and pea grain protein supplements for organic milk production - KHALILI, H.; KUUSELA, E.; SAARISALO, E. (Agricultural and Food Science, 1999)
Grass-red clover silage was fed ad libitum. In experiment 1 a duplicated 4 x 4 Latin square design was used. A mixture of oats and barley was given at 8 kg (C). Three isonitrogenous protein supplements were a commercial rapeseed meal (218 g kg-1 dry matter (DM); RSM), crushed organic field pea (Pisum sativum L.) (452 g kg-1 DM; P) and a mixture of pea (321 g kg-1 DM) and organic rapeseed (Spring turnip rape, Brassica rapa L. oleifera subv. annua) (155 g kg-1 DM; PRS). Cows on P and PRS diets produced as much milk as cows on the RSM diet. Milk yield was higher but protein content lower with PRS diet than with diet P. In experiment 2 a triplicated 3 x 3 Latin square design was used. A mixture of oats (395 g kg-1 ), barley (395 g kg-1 ) and a commercial heat-moisture treated rapeseed cake (210 g kg-1 ) was given at 8 kg (RSC). The second diet (ORSC) consisted (g kg-1) of oats (375), barley (375) and cold-pressed organic rapeseed cake (250). The third diet (RSCO) consisted (g kg-1) of oat (395), barley (395) and commercial heat-moisture treated rapeseed cake (250) and additional rapeseed oil (0.38 kg) to balance fat content between ORSC and RSCO diets. There was no dietary effect on the yield of energy corrected milk. Milk yield was higher with RSCO diet compared with other diets.;